Technological intensity and innovation capability in industrial firms. Issue 2 (17th July 2018) - Zawislak, Paulo Antônio; Fracasso, Edi Madalena; Tello-Gamarra, Jorge
Abstract : Purpose: Over time, technological intensity has been used as a proxy for innovation capability of firms in an industrial sector. However, not only firms belonging to the stratum of high technological intensity are able to innovate. Therefore, this study aims to explore a potential association between technological intensity and innovation capability in firms from different industrial sectors, using the Organization for Economic Cooperation and Development (OECD)'s classification and the components of innovation capability proposed by Zawislak et al . (2012, 2013). Design/methodology/approach: The authors conducted an exploratory research with four case studies focusing on the innovation capability of Brazilian firms. Findings: The results show that the four firms, each belonging to one stratum of technological intensity, have innovation capability, and the differences regarding this feature can be explained by the balance and development of all firms' capabilities (technological, operational, managerial and transactional). Originality/value: In the literature, studies that relate technological intensity and innovation capability are scarce. Therefore, the originality of this research is to relate these two concepts. The most important is that firms can be innovative regardless of their stratum of technological intensity, which shows the importance of other capabilities to ensure the innovation's success.